Ethnicity impact on oral processing behaviour and glycemic response to noodles: Chinese (Asian) vs. New Zealander (Caucasian) - Jin, Xiaoxuan; Lin, Suyun; Gao, Jing; Kim, Esther H.-J.; Morgenstern, Marco P.; Wilson, Arran J.; Agarwal, Deepa; Wadamori, Yukiko; Wang, Yong; Ying, Jian; Dong, Zhizhong; Zhou, Weibiao; et al. (Food & function, 2022)
There is an increasing awareness of the link between food breakdown during chewing and its nutrient release and absorption in the gastrointestinal tract. However, how oral processing behaviour varies among different ethnic groups, and how such difference further impacts on bolus characteristics and consequently glycemic response (GR) are not well understood. In this study, we recruited a group of Asian (Chinese) subjects in China ( n = 32) and a group of Caucasian subjects in New Zealand ( n = 30), both aged between 18 and 30 years, and compared their blood glucose level (BGL) over 120 min following consumption of a glucose drink and cooked white noodles. We also assessed their chewing behaviour, unstimulated saliva flow rate, and ready-to-swallow bolus characteristics to determine whether these measures explain the ethnic differences in postprandial glycaemia. Compared to New Zealand subjects, the Chinese subjects showed 35% slower saliva flow rate but around 2 times higher salivary α-amylase activity in the unstimulated state. During consumption of noodles, Chinese subjects on average took a larger mouthful size, chewed each mouthful for longer and swallowed a larger number of particles with a smaller particle size area. Total GR measured by area under the curve (IAUC) was higher among the Chinese subjects. They also experienced higher BGL at 15 min, as well as higher peak BGL. There were strong correlations observed between oral processing and GR parameters. Results of this study confirmed the significance of oral processing in determining food digestion, and will provide new insights on the role of ethnicity in influencing people's physiological response to food.